2011
DOI: 10.1093/eurpub/ckr055
|View full text |Cite
|
Sign up to set email alerts
|

Young age at first intercourse and risk-taking behaviours--a study of nearly 65 000 women in four Nordic countries

Abstract: Young age at first intercourse is associated with subsequent risk-taking behaviours. Our study emphasizes the importance of targeting prevention efforts towards the complexity of risk-taking behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 23 publications
5
41
1
3
Order By: Relevance
“…Younger age at first sexual intercourse is associated with increased risk for sexually transmitted diseases and risk-taking behavior, such as smoking and binge drinking. 27 Prematurity on the other hand is associated with personality profiles in adulthood characterized by over-controlling or inhibited tendencies, such as cautiousness, dutifulness, and fewer risk-taking or fun-seeking behaviors. 18,26,[28][29][30] Adolescents who have over-controlling tendencies have fewer intimate relationships, 31 and individuals who have inhibited tendencies have lower likelihood of having a stable romantic partner in young adulthood and get involved with such relationships later than control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age at first sexual intercourse is associated with increased risk for sexually transmitted diseases and risk-taking behavior, such as smoking and binge drinking. 27 Prematurity on the other hand is associated with personality profiles in adulthood characterized by over-controlling or inhibited tendencies, such as cautiousness, dutifulness, and fewer risk-taking or fun-seeking behaviors. 18,26,[28][29][30] Adolescents who have over-controlling tendencies have fewer intimate relationships, 31 and individuals who have inhibited tendencies have lower likelihood of having a stable romantic partner in young adulthood and get involved with such relationships later than control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Se consideró DST a la primera relación sexual con penetración anterior a los 15 años, coincidiendo con la edad media de debut sexual de los participantes y con estudios anteriores (Olesen et al, 2011;Pettifor, Van der Straten, Dubar, Shiboski y Padian, 2004;Potdar y Mmari, 2011). En España la edad de debut sexual se sitúa en torno a los 15 años (Castro et al, 2011;Teva et al, 2009), unos años por debajo respecto a muestras con cohortes de mayor edad (de Sanjosé et al, 2008;Wellings et al, 2006) y estudios internacionales Haydon, Herring, Prinstein y Halpern, 2011).…”
Section: Discussionunclassified
“…En España, un elevado porcentaje de jóvenes debuta sexualmente alrededor de los 15 años (Espada, Morales, Orgilés, Piqueras y Carballo, 2013;Espada, Orgilés, Morales, Ballester y Huedo-Medina, 2012;Teva, Bermúdez y Buela-Casal, 2009). Diversos estudios señalan la relación entre la edad de debut sexual y el riesgo sexual, en términos de contraer una ITS (Olesen et al, 2011;Schofield, Biernman, Heinrichs y Nix, 2008;Tenkorang y Maticka-Tyndale, 2008) y tener un embarazo no deseado y/o aborto (Cooper et al, 2007;Ma et al, 2009). El debut sexual anterior a los 13 años incrementa dos veces la probabilidad de infectarse por el VIH respecto a quienes tienen la primera experiencia sexual a los 17 años (Kaestle, Halpern, Miller y Ford, 2005).…”
Section: Introductionunclassified
“…This result was also observed in a study that analyzed the recurrence of adolescent pregnancy in the state of Ceará, where the exchange of partners was associated with a risk condition for subsequent pregnancy, increasing the probability of a new pregnancy 40 by about 40%. Another study with adolescents from four Nordic countries found that the odds of reporting more than ten lifetime sexual partners were four times higher among women reporting early onset of sexual intercourse compared to those reporting age over 14 years on the occasion of the first intercourse 23 . Association between the diversity of partners and exposure to pregnancies may be related to the difficulty of negotiating contraceptive use with each new relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Anticipation of first sexual intercourse has been pointed out as a relevant factor for a series of negative implications in the life of young people, such as exposure to STIs 23 , unplanned pregnancies 24 , alcohol abuse and tobacco use 23 . These implications suggest the need to adopt health education strategies so that young people are sensitized to postpone the onset of sexual life.…”
Section: Discussionmentioning
confidence: 99%